Kemampuan Pemecahan Masalah High Order Thinking Skill Siswa Kelas VIII SMP Negeri 6 Mataram Tahun Pelajaran 2020/2021 Ditinjau Dari Prestasi Belajar Siswa - Sangga Patih Alam; Sripatmi Sripatmi; Baidowi Baidowi; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The research was aim to describe the ability of class VIII SMP Negeri 6 students 2020/2021 academic year in solving problems on HOTS questions nased on student learning achievement. This research is classified as qualitative-descriptive research. The subjects of this research were 37 students of class VIII D and VIII E of SMP Negeri 6 Mataram on the 2020/2021 academic year, the subjects were grouped according to the results of a high, medium, and low mathematics learning achievement by using results of the odd semester test for the 2020/2021 academic year as the reference. Data collection techniques used is test techniques and interview techniques. The test technique is 2 HOTS solving ability questions for number pattern material. The interview technique was used to obtain detailed information about the students' views on problem-solving steps on the questions. The results of HOTS problem-solving ability test were analyzed according to Polya stages of problem-solving abilities. Based on the results of data analysis of groups with high learning achievement students, 75% of students met the indicators of the stages of understanding problems and planning solutions, 100% of students fulfilled the stages of completing settlements, and no students were able to meet the stages of re-examination. From the group of students with moderate learning achievement, 70.6% of students were able to meet the stages of understanding the problem, 58.8% of students met the stages of planning a solution, and 35.3% of students fulfilled the stages of solving problems and checking back. From the group of students with low learning achievement, only 6.3% of students were able to fulfill the stages of understanding the problem, the rest were unable to fulfill the four stages of problem-solving Polya.